Implementation of Social Assistance for Persons with Intellectual Disabilities - Dedek Roslina; Ety Rahayu (Asian Social Work Journal, 2019)
Distance Service Program (DSP) is a community based rehabilitation program for persons with intellectual disabilities. This program has been running 11 years and is considered able to improve the wellbeing of persons with intellectual disabilityies and their families. In 2017, DSP implemented in West Bandung regency by rehabilitating 30 persons with intellectual disability. At the end of the program, beneficiaries receive cash aid to be managed as productive economic business capital. This article discusses the process by which the beneficiary families together with community cadres in managing the social assistance. The research method used is qualitative with descriptive research type. 13 selected informants represent program managers, program implementers, and program beneficiaries. The results of the field findings indicate that the beneficiary families of DSP 2017 have used the cash aid in accordance with the plan. Most of them are able to manage productive economic business and supplement family income by involving beneficiaries. The findings also reveal participatory economic empowerment by maximizing the potential of intellectual disabilities. However, there are also some types of endangered businesses consumed, dead fowls exposed to the virus, and businesses that take a long time to earn income for the family.